Effects on Soil Aggregates and Organic Carbon Under a Triple-Cropping System in the Middle Reaches of the Yangtze River - Binjuan Yang; Qin Liu; Ning Liu; Yao Huang; Guoqin Huang (Agronomy)
Soil aggregate stability is an important factor that impacts ecological restoration and soil erosion. Soil organic carbon (SOC) is also an important factor affecting soil characteristics and quality. The triple-cropping system has the potential to enhance soil aggregate stability by promoting a more diverse and continuous plant cover, which could lead to improved soil structure and resistance to erosion. Over two consecutive years, this study was conducted to explore the impacts of the triple-cropping system on soil aggregate stability, soil carbon pool, and carbon sequestration characteristics in the middle reaches of the Yangtze River. This study set up five planting modes, namely milkvetch–early rice–late rice (CRR, CK), milkvetch–early rice–sweet potato||soybean (CRI), rape–early rice–late rice (RRR), rape–early rice–sweet potato||soybean (RRI) and potato–early rice–late rice (PRR). The contribution of soil aggregates > 2 mm under CRI increased by 20.77%, 6.71%, and 2.19% to the control in winter cropping and early and late rice harvesting periods, respectively. During the winter harvest period, the geometric mean diameter (GMD) and mean weight diameter (MWD) of the CRI treatment were significantly higher than other treatments (p < 0.05), with increases of 7.53–16.28% and 4.67–10.28% respectively. After the late rice harvest, the GMD values of the CRI and PRR treatments were significantly higher than the control treatment by 13.56%, and the MWD values were higher than those of other treatments by 4.24–13.17%, 3.74–12.63% (p < 0.05). Furthermore, CRI also improved the GMD and MWD of soil aggregates, and the stability of soil aggregates was improved by winter milkvetch (treatment of CRI) and paddy-upland multi-crop models (treatment of PRR). RRR treatment was beneficial to the accumulation of soil organic carbon and slowed the loss of soil organic carbon. Irrigation and drought multiple cropping can effectively increase the content of soil active organic carbon, among which the treatment of CRI had the best performance and the most significant effect in increasing the content of soil active organic carbon. After the late rice harvest, the soil’s active organic carbon content in the CRI treatment was the highest, which was significantly different from the control treatment and increased by 35.62% compared with the control (p < 0.05). Compared with before planting, the soil microbial biomass carbon content in each treatment increased by 12.07–27.59% after the late rice harvest. The soil-dissolved organic carbon content in CRI treatment was the highest, which was significantly higher than CK treatment, RRR, and PRR, with an increase of 46.88%, 42.42%, and 30.56%, respectively (p < 0.05). In addition, the accumulation of soil microbial biomass carbon, soil dissolved organic carbon content, and soil easily oxidized organic carbon content was promoted by multi-cropping in rice fields, and the increase from CRI and RRI treatment was more significant. In conclusion, in the triple-cropping area of paddy fields in the middle reaches of the Yangtze River, the milkvetch–early rice–sweet potato||late soybean and rape–early rice–sweet potato||late soybean models are conducive to the optimal management of the soil carbon pool and carbon sequestration. These models can improve the multiple cropping index, reduce costs, and increase revenue.